Age‐Related Parkinsonian Signs in Microdeletion 22q11.2. Issue 7 (9th May 2020) - Boot, Erik; Mentzel, Thierry Q.; Palmer, Lisa D.; van Harten, Peter N.; Marras, Connie; Lang, Anthony E.; Bassett, Anne S.
Abstract: Background: The recurrent hemizygous 22q11.2 deletion associated with 22q11.2 deletion syndrome has been identified as a genetic risk factor for early‐onset PD. However, little is known about early motor signs in this condition. Objectives: We examined the presence, severity and possible factors associated with parkinsonism in adults with 22q11.2 deletion syndrome and without PD. Methods: We compared motor signs between 82 adults with 22q11.2 deletion syndrome and 25 healthy controls, using the MDS‐UPDRS part III, and three‐dimensional motion‐tracker technology to quantify components of bradykinesia. Results: Median MDS‐UPDRS part III total and bradykinesia subscores were significantly higher in 22q11.2 deletion syndrome (median age: 26 years; range, 17–65) than in controls ( P = 0.000; P = 0.000, respectively). Age was a significant contributor to bradykinesia subscore ( B = 0.06; P = 0.01) and to the electronic bradykinesia component, velocity ( B = –0.02; P = 0.000); psychotic illness did not significantly impact these analyses. In 22q11.2 deletion syndrome, MDS‐UPDRS–defined bradykinesia was present in 18.3%, rigidity in 14.6%, and rest tremor in 12.2%. Conclusions: Parkinsonian motor signs appear to be common and age related in 22q11.2 deletion syndrome. Longitudinal studies are needed to investigate possible symptom progression to PD. © 2020 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.